BO‘LAJAK TARBIYA FANI O‘QITUVCHISINING DEONTOLOGIK TAYYORGARLIGI VA UNI RIVOJLANTIRISH OMILLARI - Vaxobov, A.A. (SCIENCE and SOCIETY, 2024)
This article broadly analyzes the deontological training of the future teacher, his main tasks and requirements for him. The issues of determining the development of deontological competence of a future teacher based on the qualification requirements for the industry are covered. In order to further illuminate the possibilities of deontological training of a future teacher, a number of scientists have scientifically substantiated the philosophical foundations of professional ethics and morality of a teacher.
Keywords: deontology; ethics; humanity; duty; respect; responsibility; spirituality; worldview; attitude; social; adequate; ignorance; enlightenment; justice